2019
DOI: 10.2147/ott.s197535
|View full text |Cite
|
Sign up to set email alerts
|

<p>Tumor necrosis factor &alpha; knockout impaired tumorigenesis in chronic myeloid leukemia cells partly by metabolism modification and miRNA regulation</p>

Abstract: Purpose Half of the chronic myeloid leukemia (CML) patients with sustained deep molecular response suffer from relapse after discontinuation mainly because tyrosine kinase inhibitors (TKIs) cannot eradicate leukemia stem cells (LSCs). In addition, tumor necrosis factor α (TNF-α) is highly detected in CML patients. Our aim was to explore whether TNF-α is a potential target for LSC elimination. Materials and methods We applied a CRISPR/Cas9 gene editing technique, colony-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…In fact, TNF has been recognized as a key regulator at all stages of tumor malignancies, including tumorigenesis, cancer cell proliferation, survival, angiogenesis, cellular invasion, and metastasis [33]. Moreover, TNF can stimulate the release of other pro-inflammatory cytokines in larger quantities, thereby perpetuating chronic inflammatory responses [31,38,39]. Building upon this information, our study revealed that K-562 cells release elevated levels of TNF following stimulation by LPS.…”
Section: Discussionsupporting
confidence: 53%
“…In fact, TNF has been recognized as a key regulator at all stages of tumor malignancies, including tumorigenesis, cancer cell proliferation, survival, angiogenesis, cellular invasion, and metastasis [33]. Moreover, TNF can stimulate the release of other pro-inflammatory cytokines in larger quantities, thereby perpetuating chronic inflammatory responses [31,38,39]. Building upon this information, our study revealed that K-562 cells release elevated levels of TNF following stimulation by LPS.…”
Section: Discussionsupporting
confidence: 53%
“…TNFα and IL-6 have been shown to support stem and progenitor cell survival and proliferation in CML [50][51][52][53]. Additionally, several groups have reported a role for cytokines in the CML bone marrow microenvironment [53][54][55][56][57], and blockade of extrinsic survival signals was shown to restore sensitivity of CML cells to TKIs [58,59]. Since our RNA-seq data implicated TNFα signaling via NF-κB, we hypothesized that autocrine TNFα production was responsible for further NF-κB activation in TKI resistance.…”
Section: Knockdown Of Psmd1 or Psmd3 Reduced Nf-κb Protein Expressionmentioning
confidence: 78%
“…In addition, this targeting approach for oncogenic fusion genes has been successfully used to impair the BCR-ABL1 fusion protein expression in chronic myeloid leukemia K562 cell line, in vitro and on in vivo xenograft athymic nude mice models [ 67 ]. With this cell model, others have shown that tumor necrosis factor-alpha ( TNF-α ) gene knockout can markedly reduce the proliferation and clonogenic potential of K562 cells in vitro, and the edited cells displayed impaired tumor xenograft growth in mice models [ 68 ]. Furthermore, altered TNF-α function as a result of gene editing was associated with a deregulated metabolism profile.…”
Section: Approaches For Therapeutic Genome Editing In Human Malignant...mentioning
confidence: 99%
“…Furthermore, altered TNF-α function as a result of gene editing was associated with a deregulated metabolism profile. The expression profile of TNF-α knockout cells revelated differentially expressed miRNAs involved in the cell cycle, apoptosis, and other pathways associated with the malignant phenotype [ 68 ]. Altered metabolism in malignant cells is not something new, and a positive correlation between increased lipid metabolism and cancer development and progression has been established (reviewed in [ 69 , 70 ]).…”
Section: Approaches For Therapeutic Genome Editing In Human Malignant...mentioning
confidence: 99%